Optimization of Welding Parameters for Self-Support Friction Stir Welding (SS-FSW) on AA6063 Pipe Joints - Lotpy, M.A.M.N. (Springer Science and Business Media Deutschland GmbH, 2021)
The use of the friction stir welding (FSW) process with the needs of inner mandrels or backing plates will limit the further application for industrial needs. Therefore, the self-support friction stir welding (SS-FSW) technique is used to run the joining process without the inner mandrel or backing support especially for pipes. In order to execute the experiment, the AA6063 pipe with 89Â mm of outside diameter and 5Â mm of wall thickness was utilized in this experiment setting. Several edge preparations were used such as butt, scarf and stepped joint. In addition, the different pin profiles were also used: cylindrical, rectangular and triangular shape. The selected rotational speeds were 910Â rpm, 1280Â rpm and 1700Â rpm. The Taguchi L9 orthogonal array was used to minimize the number of experiments as it is difficult to conduct a high number of experiments to find out the level combinations. The height of deformation was measured and analyzed further by the use of a statistical tool, i.e. analysis of variance (ANOVA) via Minitab 19. As a result, the optimum parameters were 910Â rpm of rotational speed, rectangular pin profile and stepped joint of edge preparation, with the minimum height of deformation at 542.25Â Î¼m. The pin profiles were the major factor that can affect the output with a 62.38 of contribution. The future works will be continued until the elimination of the requirement of inner mandrel or backing plate in the use of FSW process can be achieved. Â© 2021, The Author(s), under exclusive license to Springer Nature Switzerland AG.